Volume 4: Heat Transfer, Parts a and B 2012
DOI: 10.1115/gt2012-68268
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Effects of Internal Rib and Rear Bump on Film Effectiveness

Abstract: This paper reports detailed measurement of film cooling effectiveness for a scaled up film-cooling hole with an expanded exit fed by a smooth and ribbed secondary flow channel, an arrangement typical of turbine blades. The experiments are carried out at blowing ratios ranging from 0.4 to 1.25, and ten different rib patterns including forward oriented ribs and inverse oriented ribs are evaluated. Further, to develop an efficient film-cooling technique, several kinds of bumps are installed downstream of the hole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The appearance of a pair of counter-rotating vortices in the cooling-air jet is well known as a typical flow structure in the case where the plenum chamber or the internal flow passage parallel to the external main flow is used (7) (8) . The lift-off of the counter-rotating vortices was also reported previously (19) . The appearance and evolution of the counter-rotating vortices seen in the present simulation for Rib1 seems to be quite similar to that reported in the literature.…”
Section: Cooling-air Jet Characteristicsmentioning
confidence: 75%
See 1 more Smart Citation
“…The appearance of a pair of counter-rotating vortices in the cooling-air jet is well known as a typical flow structure in the case where the plenum chamber or the internal flow passage parallel to the external main flow is used (7) (8) . The lift-off of the counter-rotating vortices was also reported previously (19) . The appearance and evolution of the counter-rotating vortices seen in the present simulation for Rib1 seems to be quite similar to that reported in the literature.…”
Section: Cooling-air Jet Characteristicsmentioning
confidence: 75%
“…The flow filed for Rib1 contains a pair of symmetrical counter-rotating vortices whereas that for Rib2 contains a pair of skewed vortices. These skewed vortices create a wall-ward flow (19) in the cooling-air jet in the region where the experimental η takes a local peak. In other words, the cooling-air jet is split into two lumps, one consisting of a pair of skewed vortices (skewed vortical lump or SVL, hereafter) and the other containing the wall-ward flow (wall-ward lump or WWL, hereafter).…”
Section: Cooling-air Jet Characteristicsmentioning
confidence: 99%
“…The semi-expansion angle g and the laid-back angle b were 10 deg. The shape of the hole with SH was based on what Renze et al [11] and Sakai et al [12] employed in their studies. This type of hole exit shape was selected because the windward half of the exit shape was almost the same as that of RH and it was easy to establish the position of DFCDs relative to the hole exit.…”
Section: Introductionmentioning
confidence: 99%
“…Nasir et al [10] and Sakai et al [11] changed the shape of the cooling holes exit to more complicated one, and tried control of the flow structure. Nasir et al [10] organized triangular tab downstream of a cylindrical hole, and reduced lift-off by changing vortex structure.…”
Section: Introductionmentioning
confidence: 99%
“…Nasir et al [10] organized triangular tab downstream of a cylindrical hole, and reduced lift-off by changing vortex structure. Sakai et al [11] clarified flow structure and temperature field when putting bump on the downstream of a cooling hole experimentally and numerically. In their study very complicated flow structures were found by CFD.…”
Section: Introductionmentioning
confidence: 99%